A música de Umbanda joseense no processo composicional - Davino, Guilherme do Nascimento [UNESP] (2020)
As an attempt towards compositions that use metalinguistic operations to create a musical discourse guided by pre-existing external references, four musical works were created: Anas, Linha de Cangaço, Giramundo, Curimba de Preto Velho. This musical works integrates the Curimba Joseense’s cycle. Musical and extra-musical materials were used to compose this cycle, resulting from an ethnomusicographic documentation on making music in the Umbanda centers localized in São José dos Campos. To highlight the semantic potential produced by metalinguistic operations, we use the concepts of interindex and extra-index proposed by the composer Willy Corrêa de Oliveira and later elucidated by his former student Maurício Funcia de Bonis.